2019
DOI: 10.3389/fbioe.2019.00225
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Controlled Release of Resveratrol Within Functionalized Mesoporous Silica Nanoparticles for Prostate Cancer Therapy

Abstract: Resveratrol (RES) is a naturally existing polyphenol which exhibits anti-oxidant, anti-inflammatory, and anti-cancer properties. In recent years, RES has attracted attention for its synergistic effect with other anti-cancer drugs for the treatment of drug resistant cancers. However, RES faces the issues of poor pharmacokinetics, stability and low solubility which limits its clinical application. In present study, RES has been loaded onto uniformly sized (~60 nm) mesoporous silica nanoparticles (MSNs) to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 48 publications
5
56
0
Order By: Relevance
“…The sizes of the MSNs thus prepared were uniform with approx. The diameter of 72 nm after modifications [168]. The zeta potential of the RES-loaded and functional group modified MSNs were in the range of −42.8 and −11.2 mV, indicating the non-aggregation in preparation.…”
Section: Res-loaded Mesoporous Silica Nanoparticles For Prostate Cancmentioning
confidence: 91%
See 2 more Smart Citations
“…The sizes of the MSNs thus prepared were uniform with approx. The diameter of 72 nm after modifications [168]. The zeta potential of the RES-loaded and functional group modified MSNs were in the range of −42.8 and −11.2 mV, indicating the non-aggregation in preparation.…”
Section: Res-loaded Mesoporous Silica Nanoparticles For Prostate Cancmentioning
confidence: 91%
“…In the development of a nano-delivery vehicle for RES, mesoporous silica nanoparticles (MSNs) has been advocated for its silanol functional groups on its surface for modification of the surface [167,168], improved pore size, and particle size, and is used in for encapsulation of hydrophilic and hydrophobic molecules. The fabricated nanoparticles of MSNs have positively charged surface amine groups and negatively charged phosphonate groups and are loaded with RES to effectively act against those cancer cells that are found resistant to Doc in PC3 cells.…”
Section: Res-loaded Mesoporous Silica Nanoparticles For Prostate Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSNs were synthesized according to a previously reported method [16]. In brief, the MSNs were synthesized by mixing 380 mL of NaOH solution (0.5 mg/mL) and 100 mL of CTAB solution.…”
Section: Preparation Of Mesoporous Silica Nanoparticles (Msns)mentioning
confidence: 99%
“…In recent studies, a few researchers focused on the naturally occurring polyphenolic compound, resveratrol (3,4,5-trihydroxystilbene) (RSVL), which was found in red wine and some Asian medicinal herbs [7]. It has been reported that RSVL exhibits the anti-oxidation, anti-in ammatory anti-aging and anticancer functions [8][9][10]. Besides, previous studies showed that RSVL could attenuate the bone loss in ovariectomy-induced osteoporosis and promote the proliferation and osteogenic differentiation of mesenchymal stem cells [11][12][13].…”
Section: Introductionmentioning
confidence: 99%